Diagnostic and Statistical Manual of Mental Disorders / DSM-5: Fifth Edition (Abingdon Press, 2013)
DSM-5 Classification, Preface, DSM-5 Basics, Introduction, Cautionary Statement for Forensic Use of DSM-5, Diagnostic Criteria and Codes, Neurodevelopmental Disorders, Schizophrenia Spectrum and Other Psychotic Disorders, Bipolar and Related Disorders, Depressive Disorders, Anxiety Disorders, Obsessive-Compulsive and Related Disorders, Trauma - and Stressor-Related Disorders, Feeding and Eating Disorders, Sleep-Wake Disorders, Sexual Dysfunctions, Gender Dysphoria, Disruptive and Impulse Control and Conduct Disorders, Sustance-Related and Addictive Disorders, Neurocognitive Disorders, Personality Disorders, Paraphilic Disorders, Other Mental Disorders, Medication-Induced Movement Disorders and Other Adverse Effects of Medication, Other Conditions that May Be a Focus of Clinical Attention, Emerging Measures and Models, Assessment Measures, Cultural Formulation, Alternative DSM-5 Model for Personality Disorders, Appendices, Index.